2021
DOI: 10.21203/rs.3.rs-332012/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Prevalence of viral and bacterial coinfections in malaria in Venezuela

Abstract: Background Malaria remains a significant public health problem worldwide. Simultaneous infections with other pathogens complicate its diagnosis and can also change the clinical course of the disease. The similarities in the clinical presentation of malaria and other infections and the superimposed endemicity result in underdiagnosis of coinfections and increase mortality. No studies have focused on the presence of coinfections in patients with malaria in Venezuela. Methods Between June and November 2018, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Thus, 9 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] that met the eligibility criteria were included. Another study [ 23 ], identified from Google Scholar, was included. Finally, 10 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were included for the qualitative and quantitative analyses ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, 9 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] that met the eligibility criteria were included. Another study [ 23 ], identified from Google Scholar, was included. Finally, 10 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were included for the qualitative and quantitative analyses ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study [ 23 ], identified from Google Scholar, was included. Finally, 10 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were included for the qualitative and quantitative analyses ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations